DAMPAK PERCERAIAN TERHADAP KELUARGA DALAM KUMPULAN CERPEN ORANG-ORANG KOTAGEDE KARYA DARWIS KHUDORI - Pardi Suratno; Sri Budiyono (LPPM Universitas Widya Dharma, 2022)
Abstract The collection of short stories from the Orang-Orang Kotagede (Kotagede People) is the work of Darwis Khudori which was published in 2012. Although some of the short stories in this anthology were written in the 1970s and 1980s, they are still worthy and interesting to study. This study focuses on describing divorce which has a negative impact on family life. There are twenty short stories in this collection and five short stories dealing with husband-wife divorce cases. The divorce resulted in negative conditions for his family. This study is classified as a literature review using a qualitative approach. The data were obtained by reading, listening, and recording techniques which were then analyzed based on the divorce story of the married couple in the story. The results of the study are in the form of conclusions which reveal that the divorce carried out by a husband against his wife has a negative impact on family life, especially on economic life, and on their children. Keywords:divorce; impact; negativ;, family